Ethiopian church forests as monitoring towers in reconstructing climate change and its impacts and to make evidence-based climate-smart restoration efforts - Mokira, Mulugeta; Gebrekirstos, Aster; Abiyu, Abrham; Hadgu, Kiros; Hagazi, Niguse; Bräuning, Achim (State of the Art in Ethiopian Church Forests and Restoration Options, 2022)
Climate change has become one of the biggest threats to nature and society, due to extreme weather events including floods, droughts, and increased frequency and intensity of dry spells. This has been causing devastating impacts on agriculture and forestry, which are the main livelihood sources in Africa. However, there is insufficient scientific information on climate change, especially as it concerns related changes in growth patterns, water use efficiency, and stress-induced mortality of tree species. Furthermore, predictions of climate change in Africa are characterized by a high degree of uncertainty due to the limited availability of long-term and high-quality climate data. Dendrochronological data can be useful to better understand forest growth dynamics, tree-to-forest level responses to changing climate, and to reconstruct multi-century climate information and characterize extreme climate events beyond instrumental periods. Although Ethiopia has lost most of its natural forest cover, church forests provide a unique source of old-growth trees that can serve as monitoring towers in multiple ways. We addressed opportunities and challenges of dendroecological application and summarized results from different studies on Juniperus procera growing in church forests. We describe dendrochronological applications for studying current climate change effects, hydroclimatic reconstructions, forest ecological research, forest rehabilitation, and carbon management. Reviewed hydroclimate and dendroecological studies confirmed that church forests are valuable archives of regional hydroclimate information and important to understand the growth dynamic of old-growth Afromontane forests. This information is required to assist evidence-based climate-smart restoration efforts. Multiple tree-ring formation per year was reported, particularly in areas with ambiguous rainfall seasonality. However, such challenges can be resolved through proper site selection, the advancement of technologies, and using newly emerging methodologies.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Carbon dynamics; Church forests; Climate reconstruction; Dendroecology; Ethiopia; Forest restoration; Growth dynamics; Remote climate-teleconnection; River flow